People with intellectual and multiple disabilities access leisure, communication, and daily activities via a new technology-aided program - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Fiore, Alessandra (Frontiers in Psychology, 2022)
People with mild to moderate intellectual or multiple disabilities may have serious difficulties in accessing leisure events, managing communication exchanges with distant partners, and performing functional daily activities. Recently, efforts were made to develop and assess technology-aided programs aimed at supporting people in all three areas (i.e., leisure, communication, and daily activities). This study assessed a new technology-aided program aimed at helping four participants with intellectual and multiple disabilities in the aforementioned areas. The program, which was implemented following a non-concurrent multiple baseline across participants design, relied on the use of a smartphone or tablet connected via Bluetooth to a two-switch device. This device served to select leisure and communication events and to control the smartphone or tablet’s delivery of step instructions for the activities scheduled. Data showed that during the baseline phase (with only the smartphone or tablet available), three participants failed in each of the areas (i.e., leisure, communication and functional activities) while one participant managed to access a few leisure events. During the intervention phase (with the support of the technology-aided program), all participants managed to independently access leisure events, make telephone calls, and carry out activities. These results suggest that the program might be a useful tool for helping people with intellectual and multiple disabilities improve their condition in basic areas of daily life.